Financial Control Behaviours a Strategy For Small and Medium Sized Business To Survive During The Covid 19 Pandemic in Pondok Melati District,Bekasi City West Java - IGP Ratih Andaningsih; Tantyo Setyowati (Edumedia Solution, 2022)
The Author in conducting this study wanted to find out how far the financial controlling behaviour have to increase quality financial in cash flow and understand the nature and scope of financial control and its important role both inside and outside organization of MSMEs in the creative economy in improving the MSMEs at Podok Melati area, Bekasi City,West Java During the Covid 19 Pandemic. The Purpose of this study isto better understand how far this qualitative descriptive research uses the content method with 25 informants on the results of long distanceinterviews from representative to financial control behaviour be able to evaluating financial performance of MSMEs actors in the Pondokmelati area sub district,Bekasi City,West Java to better understand financial controlling full empowerement properly and optimally.This research is very useful and helps MSME enterpreneurship who will increae their productivity financial performance in the creative economy,especially creative industry sector improvement of MSME business performance through a program to strenghthen MSMEs Financial control behaviour and management performance through a quality creative economic network in the creative industry sector of the small and medium business industry which is maximal and productive limitation of the the study.Research limitation in the importance of implementating,understanding and practical implementation in implementing financial and management controlling networks,especially for business unit services in the Pondok Melati area,Bekasi City,West Java.The contribution of this resarch is to improve MSMEs Financial controlling behaviour understand economic value added approaches to evaluating economic perormance and be able to compute profit quality and management quality through the creative economy of the creative industry sector a strong and profesional manner. The result of this study include financial check up and management control of MSMEs through MSME performance productivity and optimizing the growth of MSMEs business service networks and MSMEs financial and management controlling program in an integrated creative industry of economy.